ASSESSMENT INSTRUMENT MAKING TRAINING IN INTEGRATED NATURAL SCIENCE LESSON AT SMP N 43 PADANG - Annika Maizeli; Siska Nerita; Aulia Afza (STKIP PGRI Sumatera Barat, 2022)
The purpose of this community service activity is to provide assessment instrument making training in integrated natural science lesson at SMP N 43 Padang. An assessment instrument is a measuring tool used to measure a person's ability. The ability of students includes abilities in the realm of attitudes, knowledge and skills. To measure the ability of students in these three domains, appropriate instruments are needed so that educators can measure the ability of students' learning outcomes in the learning process. However, the reality on the ground is that there are still many educators at SMP N 43 Padang who still don't understand how to design an appropriate assessment instrument that fits the learning process. In this case, the community service team, lecturers of the Biology Education Study Program, PGRI University, West Sumatra, provided a solution to the problem by carrying out training in making assessment instruments in Integrated Science subjects. After training on making this assessment instrument, it is hoped that educators will be able to make assessment instruments that are in accordance with the learning process and can measure students' abilities appropriately.